PENGARUH METODE SILABA BERBANTUAN MEDIA POSTER TERHADAP KETERAMPILAN MEMBACA PERMULAAN SISWA KELAS I SDN 93 PALEMBANG - Awalia; Liza Murniviyanti; David Budi Irawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was conducted to determine the effect of the syllabus method assisted by poster media on the beginning reading skills of class I students of SDN 93 Palembang. The method used in this study is a quantitative experimental type with a One Group Pretest-Posttest Design. Data collection in this study was by means of a test question. The sample in this study was class I B as an experimental class consisting of 28 students. Data analysis in this study used the SPSS 25 application and the results showed that there was an effect of the syllabus method assisted by poster media on the beginning reading skills of class I students of SDN 93 Palembang as seen from the results of the sig output analysis (2-tailed) 0.000 <0.05 then H₀ was rejected and Hₐ was accepted. Thus, there is an effect of the syllabus method assisted by poster media on the beginning reading skills of class I students of SDN 93 Palembang.